2012
DOI: 10.1152/ajpendo.00504.2011
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon regulates ACC activity in adipocytes through the CAMKKβ/AMPK pathway

Abstract: Glucagon is important for regulating lipid metabolism in part through its inhibition of fatty acid synthesis in adipocytes. Acetyl-CoA carboxylase 1 (ACC1) is the rate-limiting enzyme for fatty acid synthesis. Glucagon has been proposed to activate cAMP-dependent protein kinase A (PKA), which phosphorylates ACC1 to attenuate the lipogenic activity of ACC1. Because AMP-activated protein kinase (AMPK) also inhibits fatty acid synthesis by phosphorylation of ACC1, we examined the involvement of AMPK and its upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…Although CaMKK2 is not expressed in mature adipocytes [44], studies have reported such expression in adipose exposed to exogenous hormonal stimulation [46,47]. In response to thyroid hormone, increased Ca 2+ concentration and AMPK activation via CaMKK2 was observed in adipocytes hypomorphic for Lkb1, an alternative upstream kinase for AMPK activation [47].…”
Section: Tissue-specific Metabolic Regulation By the Ca2+/cam-dependementioning
confidence: 99%
See 1 more Smart Citation
“…Although CaMKK2 is not expressed in mature adipocytes [44], studies have reported such expression in adipose exposed to exogenous hormonal stimulation [46,47]. In response to thyroid hormone, increased Ca 2+ concentration and AMPK activation via CaMKK2 was observed in adipocytes hypomorphic for Lkb1, an alternative upstream kinase for AMPK activation [47].…”
Section: Tissue-specific Metabolic Regulation By the Ca2+/cam-dependementioning
confidence: 99%
“…Meanwhile, CaMKK2 reportedly regulates AMPK action in response to glucagon, which then phosphorylates acetyl-CoA carboxylase 1 (ACC1) in adipocytes. Glucagon-induced phosphorylation of ACC1 attenuates its activity during FA synthesis [46]. Since increased intracellular Ca 2+ within adipocytes was not induced by glucagon, the mechanism for AMPK activation remains to be clarified and reconciled with previous findings.…”
Section: Tissue-specific Metabolic Regulation By the Ca2+/cam-dependementioning
confidence: 99%
“…Experiments on cell lines expressing the glucagon receptor have shown that stimulation of IP 3 production requires high glucagon concentrations (Xu and Xie 2009). Through mechanisms that remain incompletely understood, glucagon also activates AMP-activated protein kinase (AMPK) via Ca 2+ /calmodulin-dependent protein kinase kinase-β (CaMKKβ or CaMKK2) (Kimball et al 2004;Peng et al 2012) and p38 MAPK (Cao et al 2005), and it induces acetylation of Foxa2, an activator of lipid metabolism and ketogenesis (von Meyenn et al 2013).…”
Section: Action Of Glucagon the Glucagon Receptormentioning
confidence: 99%
“…It is therefore more easily observed in conditions of insulinopenia, and it is not clear whether or not it stimulates lipolysis under normal physiological conditions in human (Ranganath et al 2001;Arafat et al 2013;Gravholt et al 2001). Glucagon also inhibits fatty acid synthesis via an AMPK-dependent inactivating phosphosphorylation of ACC in adipocytes (Peng et al 2012).…”
Section: Main Effects Of Glucagon and Mechanisms Of Actionmentioning
confidence: 99%
“…hmCD40-RAW 264.7 cells were transfected with JNK1/2 small interfering RNA (siRNA) (Dharmacon), ULK1 siRNA (Life Technologies), CaMKK␤ siRNA (27), AMPK␣1 siRNA (27), AMPK␣2 siRNA (27), or control siRNA by using an Amaxa Nucleofector kit. Cells were subsequently transfected with a plasmid encoding tandem monomeric red fluorescent protein (RFP)-green fluorescent protein (GFP)-tagged LC3 (tfLC3) (28) (gift from T. Yoshimori, National Institute for Basic Biology, Okazaki, Japan).…”
Section: Methodsmentioning
confidence: 99%